Time to accurately determine the burden of generalized pustular psoriasis at the population level. (28th April 2022) - Choon, Siew Eng; Bachelez, Hervé
Abstract : Linked Article: Löfvendahl et al. Br J Dermatol 2022; 186 :970–976 .